Telemedicine in prenatal care - Heřman, Hynek; Faridová, Adéla; Tefr, Ondřej; Farid, Sarah; Ayayee, Noble; Trojanová, Klára; Mareš, Jindřich; Křepelka, Petr; Hanáček, Jiří; Jalůvková, Barbora; Krofta, Ladislav; Feyereisl, Jaroslav (Central European journal of public health, 2022)
Telemedicine, as a health service provided remotely, is increasingly becoming a common part of health care. Telemedicine is defined as "an umbrella term for health activities, services and systems operated remotely through information and communication technologies to promote global health, prevention and health care, as well as education, health management and health research". It also describes telemedicine as "the provision of services where distance is a critical factor, using information and communication technologies to exchange valid information for the diagnosis, treatment and prevention of disease and injury, for research and evaluation, and for the continuing education of healthcare providers to improve the health of individuals and communities". Both definitions imply that two of the hallmarks of telemedicine include the use of communication and information technologies to overcome distance as a critical factor, a factor that is well known to us, not least from the recent months of the COVID-19 pandemic. Distance medicine can thus act as a tool for improving access to health care and also complement health care itself in a very appropriate way.
Keywords: Pandemics; pregnancy; Telemedicine; telemedicína; těhotenství; COVID-19; prenatální péče; telemonitoring; Prenatal Care; ženské pohlaví; Humans; telemedicine; Pregnancy; prenatal care; pandemic; Delivery of Health Care; e-health; poskytování zdravotní péče; pandemie; Female; lidé